Meningkatkan Kognitif Siswa SMAN I Jambi Melalui Modul Berbasis E-Book Kvisoft Flipbook Maker - Mulyadi Rusli; Louis Antonius (Universitas Budi Darma, 2019)
This research was aimed to: produce module based on e-book using Kvisoft Flipbook Maker application that proper to increase learning interest and cognitive learning outcome, know the increasing interest of senior high school students which use learning media module based on e-book using Kvisoft Flipbook Maker application, and know the increasing of cognitive learning outcome of senior high school students which use learning media module based on e-book using Kvisoft Flipbook Maker application. The result show that: the module based on e-book using Kvisoft Flipbook Maker application is proper to increase learning interest and cognitive learning outcome of senior high school students seen from very good and good results category of practitioner appraisal and student’s response, the increasing of student’s learning interest which use module based on e-book using Kvisoft Flipbook Maker application by low category standard gain, and the increasing of student’s cognitive learning outcome which use module based on e-book using Kvisoft Flipbook Maker application by medium category standard gain